Images of Scientists through the Eyes of the Children - Özsoy, Sibel; Ahı, Berat (Eurasian Society of Educational Research, 2013)
The purpose of this study is to determine primary school students’ images of scientists. As research approach, the survey method, which is frequently used to learn about people’s attitudes, beliefs, values, demographics, behavior, opinions, habits, desires, ideas and other types of information, was used. The study was conducted in the spring semester of 2011- 2012 academic year with primary school students enrolling through the first grade to the fifth grade. The data of the study were collected by a Draw-A-Scientist-Test. When scoring a DAST drawing, the raters coded each indicator with either 1 or 0 points depending on the presence or absence of the feature under examination. Drawings revealed that although there are variations from individual to individual, children hold common stereotypical images of scientists. The overwhelming majority of drawings were of male scientists. Children also produced images that represent individuals with messy hair, wearing glasses, wearing a laboratory coat. Also children depicted that scientists usually work in indoors, usually in a laboratory, and perform experiments.

Bu çalışmanın amacı, ilk beş sınıfa devam eden öğrencilerin bilim insanı algısını belirlemektir. Bu araştırmada, var olan durumu en net şekilde ortaya koyabilmek amacıyla tarama modeli kullanılmıştır. Çalışma 2011-2012 eğitim öğretim yılında ilk beş sınıfa devam eden 1174 öğrenci ile yürütülmüştür. Çalışmanın verileri ‘Bir Bilim İnsanı Çiz Testi’ ile toplanmış, çizimler üzerinde puanlama yapılırken incelenen özelliğin varlığına veya yokluğuna bağlı olarak 1 veya 0 puan ile kodlanmıştır. Çizimlerden elde edilen sonuçlar, öğrencilerin sahip olduğu bilim insanı imajlarında ortak noktaların olduğunu göstermiştir. Öğrencilerin büyük bir çoğunluğu resimlerinde erkek bilim insanına yer verirken, bilim insanının fiziksel özelliklerini dağınık saçlı, gözlüklü ve laboratuar önlüğü giyen bireyler olarak tanımlamışlardır. Çalışmadan elde edilen sonuçlar ayrıca öğrencilerin çizimlerinde bilim insanlarının genelde iç mekânlarda, çoğunlukla laboratuarda çalıştığını ve deney yaptıklarını vurguladıklarını göstermiştir.

Ozsoy, Sibel (Aksaray, Yazar)
Keywords: Bilim; Science; Image of Scientist; Bilim İnsanı; Draw a Scientist Test; Bir Bilim İnsanı Çiz Testi; Scientist; Bilim İnsanı Algısı